MATERIAL OF COMETARY NUCLEI AND ASTEROIDS CAN BE STUDIED IN THE EARTH’S ORBIT - A. P. Vidmachenko; A. F. Steklov (Odessa Astronomical Publications, 2019)
The Solar system is formed from a pri- mary gas-dust cloud. Asteroids and cometary nuclei are made of the same substance. Therefore, the study of their debris will help determine their properties. It is best to investigate the substance of meteoroids in the laboratory. The presence of radioactive chemical elements in meteor- ites provides important information about their age. The study of the isotopic composition and content of uranium and thorium gives an age of a meteorite substance of 4.6 billion years. Measurement of cosmogenic isotopes in meteorites and analysis of their content allows us to de- termine the size, mass and age of meteoritic bodies before falling to Earth. By measuring the content of tritium and helium in a meteorite, the average intensity of the cosmic rays bombarding the sample is estimated. Every day, 100- 1000 tons of meteorite material falls on the Earth’s sur- face. A large mass falls to the surface under the action of meteor showers. Meteor showers are formed from the remnants of the nuclei of known comets and asteroid bod- ies. To study the substance of the nucleus of comet Chur- yumov-Gerasimenko, a spacecraft was sent to it worth about 1 billion euros. We offer, that to study the material of some nuclei of comets and asteroids, it is possible to take meteoroid samples directly in outer space in the Earth’s orbit. There, meteoroid particles must be captured, preserved and delivered to Earth for a thorough study. To capture matter from a specific parent cometary nucleus or asteroid in outer space, traps made of silicon dioxide, which are filled with airgel, can be used. The material of the traps allows you to capture particles flying at high speed without overheating them. This allows you to save organic and other molecules in such particles. Such traps should be activated at the moments of maximums of the selected meteor showers.